Adjuvant treatment for pancreatic cancer - Klaiber, Ulla; Hackert, Thilo; Neoptolemos, John P. (Translational gastroenterology and hepatology, 2019)
Pancreatic cancer is the third leading cause of cancer-associated mortality in Western countries. Upfront resection with adjuvant chemotherapy is the treatment of choice in resectable tumors, offering the chance for cure. Until the 1990s, adjuvant therapy was not routinely used after resection for pancreatic cancer. During the last three decades however, enormous progress has been made in evidence-based onco-surgical management of resectable pancreatic cancer. Based on the results from multicenter randomized controlled trials, primarily initiated by the European Study Group of Pancreatic Cancer (ESPAC), adjuvant chemotherapy has become the gold standard after upfront resection, while adjuvant chemoradiotherapy is not recommended. Combination chemotherapy with gemcitabine and capecitabine was shown to significantly prolong median overall survival after resection compared to monotherapy with either gemcitabine or 5-fluorouracil/folinic acid. Recent data from the French-Canadian Uni-Cancer GI PRODIGE 24/CCTG PA.6 trial showed that adjuvant poly-agent chemotherapy with modified FOLFIRINOX achieved median survival times of 54.4 months in selected patients. Despite improved survival times after resection followed by adjuvant chemotherapy, however, recurrence occurs still in more than 75% of patients within the first 2 years after resection. Further efforts are therefore to be made in early detection tools, the evaluation of neoadjuvant strategies, the development of new drug targets, and stratification strategies to better select patients for the available therapies. This review article summarizes the body of evidence on adjuvant treatment for pancreatic cancer, identifies evidence gaps and provides future perspectives.
Gesehen am 17.07.2020